Hubungan Antara Tingkat Spiritual Dengan Tingkat Depresi Pada Lansia Di Wilayah Kerja Dinas Sosial Surabaya - Hidayatus Sya’diyah; Wiwiek Liestyaningrum; Dhian Satya Rachmawati; Sukma Ayu Candra Kirana; Yoga Kertapati; Diyan Mutyah; Mohammad Fathur Andreyanto (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
The elderly will experience changes both biologically, psychologically, socially, and spiritually. Spiritual needs are the need to find meaning and purpose in life, the need to love and be loved and the sense of attachment and the need to give and get. This study aims to determine the relationship between the spiritual level with the incidence of depression in the elderly in the Surabaya Social Service Work Area. The design of this research was analytic observational design with cross sectional approach. Samples were taken using Probability Sampling Technique with Simple Random Sampling approach and obtained a sample of 113 elderly people at UPTD Griya Werdha Jambangan and 18 elderly people at UPTD Liponsos Keputih Surabaya. This research instrument uses DSES (Daily Spiritual Exercise Scale) and GDS (Geriatric Depression Scale) Data analysis using Spearmen's Rho Test with the level ρ <α = 0.05. The results showed that the relationship between the spiritual level with the incidence of depression in the elderly with the Spearmen's Rho test results ρ = 0.00012 (ρ <0.05) and the correlation coefficient r = +0.372 which means that there is a low relationship (0.60 - 0.80) between the spiritual level variables with the incidence depression in the elderly. Results of the study. So it can be concluded that there is a relationship between the spiritual level with the incidence of depression in the elderly in the work area of the Surabaya Social Service.Keywords: Elderly, Spiritual, Depression